Analisis Transaksi Mobile Banking Bank Syariah terhadap Perilaku Konsumtif Nasabah BSI Soloraya - Berliana Sukmawati; Waluyo (Universitas Muhammadiyah Surabaya, 2024)
Abstract In this era of information technology, the behavior of customers or consumers has changed a lot in conducting banking transactions, mobile banking is one of the types of services that banks provide to their customers in order to make it easier to carry out banking transactions anywhere because many customers put forward the convenience and encourage customers to behave consumptively in online transactions. The purpose of this study was to determine the form of mobile banking transactions of Sharia bank customers, what factors influence the consumers' behavior in using mobile banking, and the consumption behavior in mobile banking transactions of BSI customers was reviewed in the perspective of Islamic economics. This type of research is qualitative descriptive research, using a phenomenological approach, to collect data, and researchers dive directly into the field to obtain primary data sources using observation and interview methods to interviewees. The results of this study show that: 1) The form of mobile banking transactions of BSI KC Solo customers is almost the same as mobile banking in general, which distinguishes that there are Islamic services on BSI Mobile, 2) The advantages and convenience that exist such as the availability of 24-hour services and security, which is another factor, namely the income factor, 3) Some BSI KC Solo customers behave consumptively in using mobile banking where this does not correspond to the economic price Islam. Keywords: Mobile banking, Consumptive Behavior, Customer, Sharia Bank